The Relationship of Perception and Customer Satisfaction with Competitiveness of Suckling Pig Restaurant in Gianyar Regency - P. T., Hestiani; Suparta, I N.; Budaarsa, K. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
Bali is famous for many types of traditional food, one of which is famous is suckling pig. Since ancient times suckling pig has been used as a means of religious ceremonies. A long with the development of the era and the increase in the number of population not only for ceremonies but many suckling pig that have been consumed by the public. Gianyar and Ubud Subdistricts as one of the mobility and tourism areas that are growing rapidly, seems to provide opportunities for the development of restaurant businesses, especially suckling pig. The purpose of this study is to find out about the relation, preception and satisfication of customer to competitiveness of suckling pig restaurant in Gianyar Regency. This study conducted for 12 weeks at suckling pig restaurant in Gianyar Regency. Election of location determined Purrposive method and election of sampling used Accidental Sampling method. Respondents of this study as many as 80 respondens who consumed suckling pig. Variables observed are perception, satisfication, and competitiveness of suckling pig restaurant. The result of this study showed perception of customer to suckling pig culinary is in high category with 75.73% average. Satisfication of customer to suckling pig culinary is in high category with 76.27% average. Competitiveness of suckling pig restaurant is in high category with 68.52 % average. Relation between perception to competitiveness of suckling pig restaurant has obivious significant (P<0,01). Relation between satisfication to competitiveness suckling pig restaurant has significant (P<0,05). According to the result of this study could be recommended, producers have to understand the standards of consumer needs so that restaurants can provide products that match or exceed consumer needs. Keyword:Perception, satisfication, competitiveness, suckling pig